In-vitro Study Comparing the Shear Bond Values of Zirconia-reinforced Glass Ionomer Cement and Conventional Glass Ionomer Cement (Academia Journal of Medicine, 2024)
The goal of the current study was to compare the shear  bond values of zirconia-reinforced glass ionomer cement  and conventional glass ionomer cement. A collection of 20  extracted premolars with unbroken buccal or lingual  surfaces was made. The whole sample was randomly split into two groups: Group A (n=10) which was Conventional  Glass Ionomer Cement and Group B (n=10) which was  Zirconia Reinforced Glass Ionomer Cement (Zirconomer).  The process of thermocycling was used to mimic oral  conditions.
Keywords: GlC; Zirconomer; Shear Bond